An investigation on the natural rate of crime rates with Fourier panel unit root test in selected emerging economies - Uzuner, Gizem; Yildiz, Bunyamin Fuat; Mercan, Murat Anil; Wong, Wing-Keung (EMERALD GROUP PUBLISHING LTD, 2024)
PurposeThe specific objective of the study is to investigate the presence of natural rate of crime rates in selected emerging economies by using panel unit roots. The majority of the literature examines the issue using conventional unit root tests in a country-specific context. Meanwhile, there is no panel unit root investigation has been undertaken considering both cross-sectional dependence (CD) and structural changes.Design/methodology/approachAs a result, this study is to fill the aforementioned gap and validate the natural rate of crime rates for 10 countries by using a Fourier panel unit root test. The advantage of the test is that structural shifts are modelled as gradual or smooth changes with a Fourier approximation, and it also accounts cross-sectional dependency. Thus, the Fourier panel unit root test may have better performance in capturing potential changes in the nature of data.FindingsThe result of the conventional unit roots test shows evidence of the hysteresis effect in crime, as it stands does not adequately account for smooth transitions or breaks. On contrary, the Fourier panel unit root test confirms the natural rate hypothesis in crime rates. The present results highlight the detrimental effects of crime cannot be abated by short-run deterrence policies.Originality/valueContrary to previous studies, the theoretical implications of the study imply that the empirical models consider the dynamic nature of crime rates should account for natural rate properties instead of the hysteresis assumption.
Keywords: Crime rates; Crime hysteresis; Panel Fourier unit root test; Emerging economies; A12; A14; K42; STATIONARITY TEST; LEVEL; DETERRENCE; NORMALITY; SHIFTS; POWER; US; Computer Science